2D Barrier in a Superconducting Niobium Square - Joya, Miryam R.; Sardella, Edson [UNESP]; Barba-ortega, J.; Pintilie, L.; Mitoseriu, L.; Alexe, M. (Amer Inst Physics, 2014)
The presence of barriers changes the vortex structure in superconducting Nb square in presence of a uniform applied magnetic field. The Cooper pair configurations in a mesoscopics superconducting square of Nb with a barrier are calculated within the nonlinear Ginzburg Landau equations. We predict the nucleation of multi-vortex states into the sample and a soft entry of the magnetic field inside and around into the barrier. A novel and non-conventional vortex configurations occurs at determined magnetic field.